Design and implementation of multi-core cable tester with multi analyzer - keerthika, R.; kavya, G. (International Journal of Psychosocial Rehabilitation, 2020)
In this paper presented a cable tester in a single desk to improve the timing of the checking the quality of cable in single desk. Cabling is an important and expensive in business and mostly it treated in safe manner. Normally structured cabling design and placing is over viewed by a predefined standards specified by wiring data centers, commercial places and communication cable for data or voice. An IEC stands for a type of electronic cable that meets different standards and different specification. The major objective of cables is to give the physical linkage of Electronic/Electrical appliance to its power/data sources. A predefined set of templates the system could check and verify correctly and quickly by analysing the cable various faults in single desk, open circuit test, short circuit test, sequence test. In order to improve the outcome of the product in single day the above test will complete the task with duration of minimum 2 minutes and maximum 7 minutes based on the number of sockets/ports and these activities are monitoring and updates in cloud through IOT for statistics analysis of quality and quantity.